ARID2 Deficiency Enhances Tumor Progression via ERBB3 Signaling in TFE3-Rearranged Renal Cell Carcinoma - Jinglong Tang; Shintaro Funasaki; Hidekazu Nishizawa; Shoichiro Kuroda; Takanobu Motoshima; Chang Wu; Amany Sayed Mawas; Yorifumi Satou; Yuichiro Arima; Hisashi Hasumi; Ryosuke Jikuya; Kazuhide Makiyama; et al. (Current Issues in Molecular Biology)
TFE3-rearranged Renal Cell Carcinoma (TFE3-RCC) is an aggressive subtype of RCC characterized by Xp11.2 rearrangement, leading to TFE3 fusion proteins with oncogenic potential. Despite advances in understanding its molecular biology, effective therapies for advanced cases remain elusive. This study investigates the role of ARID2, a component of the SWI/SNF chromatin remodeling complex, in TFE3-RCC. Through a series of in vitro and in vivo experiments, we confirmed that ARID2 acts as a tumor suppressor in TFE3-RCC. ARID2 knockout (KO) enhanced TFE3-RCC cell migration, proliferation, and tumor growth. Transcriptomic analysis revealed ERBB3 as a key target gene regulated by both PRCC-TFE3 and ARID2. Chromatin immunoprecipitation (ChIP) assays demonstrated that PRCC-TFE3 directly binds to and upregulates ERBB3 expression, with ARID2 KO further enhancing this effect. TFE3-RCC ARID2 KO cells exhibited significant gene expression enrichment in MAPK and ERBB3 signaling pathways. These cells also showed increased activation of ERBB3, EGFR, and selective activation of SRC and MAPK. TFE3-RCC ARID2 KO cells demonstrated heightened sensitivity to the ERBB3 inhibitor AZD8931 compared to their wild-type counterparts, exhibiting significantly reduced migration and proliferation rates. These findings suggest that the PRCC-TFE3-ARID2-ERBB3 axis plays a critical role in TFE3-RCC pathogenesis and highlights the potential of targeting ERBB3 in ARID2-deficient TFE3-RCC as a therapeutic strategy. This study provides new insights into the molecular mechanisms of TFE3-RCC and suggests avenues for precision treatment of this aggressive cancer.